Sustainable aquaculture and sea ranching with the use of vaccines: a review - Alfatat, Alma; Amoah, Kwaku; Cai, Jia; Huang, Yu; Fachri, Muhammad; Lauden, Hagai Nsobi; Lyu, Shaoliang; Wang, Xuefeng; Maulu, Sahya; Asiedu, Berchie; Syaifiuddin, Syaifiuddin (Frontiers in Marine Science, 2025)
As aquaculture takes on a major role in global seafood production, the industry has encountered several hurdles, notably in disease management and overharvesting in natural habitats challenges. Vaccination is a critical component of immunological preventive strategy essential for the health management of animals. Over the past two decades, vaccines have revolutionized the sector by addressing these issues while enhancing productivity and ecological balance. Advanced vaccine technologies, including DNA, recombinant, and inactivated vaccines, have demonstrated their potential to transform aquaculture and sea ranching. Innovations like the recombinant DNA vaccine for goldfish using the G protein expressed by baculovirus for spring viremia for carp and the ME-VAC Aqua Strept vaccine for tilapia highlight their ability to reduce antibiotic dependence and support greener practices. Multivalent vaccines in salmon farming further showcase their effectiveness in improving fish health and productivity. Emerging solutions such as plant-based and mucosal vaccines offer scalable, cost-effective options for immunizing large fish populations, reducing disease-related losses, and stabilizing seafood supply chains. Vaccines also improve the survival rates of hatchery-reared fish in natural habitats, supporting long-term sustainability. By integrating vaccination with selective breeding for disease resistance, aquaculture can achieve enhanced productivity and reduced environmental impact. The article highlights the impact vaccines can have on technology leap forward and research cooperation that will allow for collective mobilization to prevent aquatic disease. Not only that, this review also discusses the challenges and opportunities of using vaccines to increase fish resilience for surviving in open waters. Emphasis on the transformative role of vaccines in enabling technological advancements, fostering research collaborations, and addressing economic and environmental challenges to ensure a sustainable future for aquaculture and sea ranching have been highlighted as well. Future research directions and economic implications of widespread vaccine adoption in aquaculture are also discussed.